2019
DOI: 10.1021/acsami.9b16428
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-, 90Y-, and 177Lu-Labeled Iron Oxide Nanoflowers Designed for Potential Use in Dual Magnetic Hyperthermia/Radionuclide Cancer Therapy and Diagnosis

Abstract: Development of a complex based on iron oxide nanoparticles (IONPs) for diagnosis and dual magnetic hyperthermia/radionuclide cancer therapy accomplishing high yields of radiolabeling and great magnetic heat induction is still a challenge. We report here the synthesis of citric acid, poly­(acrylic acid) (PAA) and poly­(ethylene glycol) coated IONPs and their labeling with three radionuclides, namely, technetium (99mTc), yttrium (90Y), and lutetium (177Lu), aiming at potential use in cancer diagnosis and therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 49 publications
(71 reference statements)
2
34
0
Order By: Relevance
“…The research on the use of HiSMF technology in magnetotherapy in clinics has been increasing due to its useful effects in many diseases, including cancers, edema, inflammation, wounds healing, and bone disorders [7][8][9][10]26]. Due to its safety and noninvasiveness, magnetotherapy has been approved as an instructive novel strategy by the US Food and Drug Administration (FDA) [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on the use of HiSMF technology in magnetotherapy in clinics has been increasing due to its useful effects in many diseases, including cancers, edema, inflammation, wounds healing, and bone disorders [7][8][9][10]26]. Due to its safety and noninvasiveness, magnetotherapy has been approved as an instructive novel strategy by the US Food and Drug Administration (FDA) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the use of MRI with 7 T in clinical diagnosis has been approved by the Food and Drug Administration (FDA) [6]. At the same time, the high-intensity magnetotherapy, a noninvasion approach, has been applied in the treatment of various diseases including osteoporosis [7], rheumatoid arthritis [8], diabetic wound healing [9], and cancer [10]. Therefore, the application of HiSMF medical equipment is megatrends in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…The zeta potentials of HA-MNP and MNP were determined using a Malvern Zetasizer Nano Z (Malvern, Worcestershire, UK). The recorded zeta potentials of HA-MNP and uncoated MNP at different pH values ranging from 2 to 11 were fitted to a Boltzmann sigmoidal function to obtain the isoelectric points [35]. The zeta potentials of HA-MNP in the presence of As(V) before and after the treatment were also measured.…”
Section: Characterization Of Synthesized Materialsmentioning
confidence: 99%
“…The development of superparamagnetic iron oxide nanoparticles (SPIONs) for diagnosis and/or bimodal cancer therapy, using magnetic hyperthermia and radionuclides, has grown considerably over recent years [47][48][49][50]. Mokhodoeva and collaborators described the incorporation of 223Ra (radium-223), the first clinically approved alpha-emitter, into SPIONs.…”
Section: Heating Modalities Used To Induce Hyperthermiamentioning
confidence: 99%
“…It was postulated that the nanoparticles with high energy beta emitters 90Y and 177Lu can be a promising system for magnetic hyperthermia and radionuclide therapy. On the other hand, SPIONs with 99mTc could be used for diagnostic imaging purposes [49]. Studies by Pospisilova and collaborators reported the incorporation of radionuclide 59Fe (iron-59) into SPIONs [50].…”
Section: Heating Modalities Used To Induce Hyperthermiamentioning
confidence: 99%